PANDANGAN HUKUM PIDANA ISLAM DAN HUKUM POSITIF TERHADAP EKSPLOITASI LANSIA PENGEMIS ONLINE - Yuli Kasmarani; Muhammad Torik; Rian Saputra (Universitas Islam Negeri Raden Fatah Palembang, 2023)
This research aims to analyze the phenomenon that occurred during the Covid-19 pandemic which required people to work to make money without having to interact directly in the real world. This is the basis for the emergence of creative ideas for content creators to use social media to earn money. As happened recently, content creators use elderly people to become actors in a live streaming video on TikTok media. If seen from the content creator's point of view, it is very profitable, because when the video goes viral and can attract the sympathy of the audience, the audience will not hesitate. to give gifts. It's different for the elderly actor who takes extreme measures such as soaking in dirty water and mud for hours just to get sympathy and gifts. The focus of the research is the views of Islamic criminal law and positive law regarding the exploitation of elderly beggars online. This research is library research or what is called normative juridical. The data source used is secondary data. The data collection technique used is document or literature study, then the data is analyzed descriptively qualitatively. The results of the research show that in Islamic criminal law the content creator has committed slavery which ignores the health of the elderly in order to gain profit, so that he can be subject to ta'zir sanctions, namely sanctions given by Ulil Amri or the government. Meanwhile, from a positive legal perspective, perpetrators/content creators of online exploitation of elderly beggars can be sentenced to imprisonment for a minimum of 3 years, a maximum of 15 years. And a fine of at least Rp. 120,000,000.00 (one hundred and twenty million rupiah) and a maximum of Rp. 600,000,000.00 (six hundred million rupiah). Keywords: Exploitation, Elderly, Online Begging, Islamic Criminal Law, Positive Law.